Response of cucumber (Cucumis sativus L. Cv. Bhaktapur local) to the application of plant growth regulators in plastic tunnel - Dahal, K.; Dahal, K. C. (Journal of Agriculture and Forestry University, 2022)
The field experiment was conducted to know the yield performance of cucumber var. Bhaktapur Local with the application of plant growth regulators (PGRs) in the farmers’ field of Lamjung, Nepal during September to November, 2013. Five treatments (Four PGRs; NAA @10 ppm, GA3 @ 50ppm, GA3 @100ppm, MH@ 60ppm and distilled water as control) were replicated six times under walk-in plastic tunnel. The experiment was laid out in randomized complete block design. The first 30 flowers of each plant were used for the observation. PGRs were sprayed in 2-4 true leaf stage of seedling, 20 days after first spray and 10 days after second spray. The research revealed that NAA @ 10 ppm had higher effect in sex expression, fruit set and yield than rest of the treatments. GA3 @ 100 ppm had significantly higher number of male flowers and more vine growth than other treatments. Branch per plant was obtained as the highest with MH @60 ppm followed by NAA @10 ppm. The marketable fruit yield was significant with NAA @10 ppm followed by MH@ 60 ppm, GA3 @50 ppm, GA3 @100 ppm than control. It is concluded that thermo-sensitive variety of cucumber Bhaktapur Local can be grown with the use of plant growth regulators particularly, NAA@ 10 ppm, under walk-in plastic tunnels during the autumn-winter season in the mid hills of Nepal. The research further indicated that cucumber can be a profitable and a potential agriculture enterprise for the area.